UV endonuclease of Micrococcus luteus, a cyclobutane pyrimidine dimer–DNA glycosylase/abasic lyase: Cloning and characterization of the gene - Shiota, Susumu (The National Academy of Sciences of the USA, 1997)
The gene of Micrococcus luteus UV endonuclease (cyclobutane pyrimidine dimer–DNA glycosylase/abasic lyase) was cloned and characterized. The cloned gene, whose product had a predicted molecular mass of 17,120 Da, was found to be capable of complementing the Escherichia coli uvrA6 mutation in vivo with respect to resistance to acetone-mediated molecular photosensitization, a treatment producing exclusively cyclobutane pyrimidine dimers in DNA. It also generated a nicking activity specific for photosensitization-treated DNA by in vitro transcription/translation. When expressed in E. coli cells, the gene produced a protein structurally identical with UV endonuclease and possessing an activity consistent with cyclobutane pyrimidine dimer–DNA glycosylase/abasic lyase with respect to the effect of inhibitors and the site of the DNA backbone scission. Furthermore, the UV endonuclease-deficient mutant DB7 was shown to regain the enzyme through transformation with the cloned gene. The deduced amino acid sequence of the gene product was at best 27% identical with that of endonuclease V of phage T4, an enzyme strikingly similar to UV endonuclease in molecular and catalytic properties. Despite this marginal overall similarity in amino acid sequence, four of the seven amino acid residues reported to be functionally important in the T4 enzyme were found to be conserved in the M. luteus enzyme. We propose that the gene be called uveA.